DEVELOPING INTERACTIVE MULTIMEDIA MATERIAL TEXT RECOUNT ORAL AND WRITE ABOUT SIMPLE EXPERIENCES FOR EFL STUDENTS - purwo (Wiralodra English Journal, 2019)
The aims of research are: (1) to describe the condition and potency of current learning on the basic material text recount, (2) to produce teaching-learning materials Compact Disc (CD) interactive multimedia which is integrated with basic competence in the form of procedural text with manuals and tips and it was conducted at one semester students EFL Data were collected through observation, questionnaires, and tests. Analyze data uses descriptive and Gain test. The conclusions of research are; (1) EFL has the potency of using IT, tools and infrastructure of computer, teaching material to support the teaching process, (2) the process produced the product through Lectora program, (3) The teaching and learning process utilizing interactive multimedia teaching material is more effective, shown by N-Gain score 0.71, (4) after using interactive multimedia, the teaching and learning process can save 90 minutes compared to the previous lesson, (5) learning using interactive multimedia interesting, in organizing strategy (87.00%), in terms of delivery (84,97%), and in terms of program management strategies to obtain optimal learning results (85.04%).